Pengaruh Good Corporate Governance terhadap Penghindaran Pajak pada Perusahaan Sektor Kesehatan yang terdaftar di Bursa Efek Indonesia (BEI) Tahun 2016-2020 - Faza Ariska; Dwi Fionasari; Mentari Dwi Aristi (Politeknik Negeri Bengkalis, 2021)
The purpose of this study was to examine the effect of good corporate governance on tax avoidance in the health sector listed on the IDX in 2016-2020. This type of research is quantitative research with secondary data that can be downloaded through www.idx.co.id. The population in this study found 22 companies with a sample of 35 data. Sampling technique using purposive sampling and using secondary data. The theory used in this research is agency theory. The results of this study indicate that the independent board of commissioners and managerial ownership has no effect on reducing tax avoidance. Meanwhile, institutional ownership and audit committee has effect on tax avoidance. For companies in the health sector, it is hoped that this research will be an additional consideration for tax management in carrying out correct and efficient tax evasion without violating applicable tax laws. Keywords: independent board of directors, institutional ownership, audit committee, managerial ownership, tax avoidance.